Christian origins and religious studies - Reed, Annette Yoshiko (Studies in religion, 2015)
This essay reflects on the relationship between the study of the origins of Christianity and the discipline of Religious Studies in conversation with William Arnal's "What branches grow out of this stony rubbish? Christian origins and the study of religion," published in Studies in Religion / Sciences Religieuses in 2010. Extending Arnal’s call for specialists in the New Testament and early Christianity to engage Religious Studies, it explores a reorientation of perspective, towards the aim of a doubled lens from and upon both Christian Origins and Religious Studies. Particularly promising may be the interrogation of ancient and modern practices of periodization and category-creation, especially as they intersect with imperial and anti-imperial discourses about "origins," knowledge, and power.